What Can We Learn from Dissecting Tortricid Females About the Efficacy of Mating Disruption Programs? - Alan Lee Knight; Michele Preti; Esteban Basoalto (Insects)
Female mating success for the tortricids codling moth (CM), Cydia pomonella, Oriental fruit moth (OFM), Grapholita molesta, European grape vine moth (EGVM), Lobesia botrana, and five leafroller (LR) species under various mating disruption (MD) programs was reviewed at a time when new dual sex lures can provide alternative tools to assess female mating. Previous reliance on passive assessments such as tethering and virgin female-baited traps with laboratory moths are at odds with active trapping methods of wild moths. Additive factors such as delayed mating, adjustments in female behaviors, and greater levels of natural control may or may not contribute to the apparent success of MD. Current MD programs are not based solely on research, as economics and commercialization require some compromise. The complete sex pheromone blend is not always used. A delay in mating has been reported from the field with one study and suggested that reductions in fecundity would likely be minimal. There is no evidence that MD works better with low population densities. MD is an established technology, but the new dual sex lures are showing that the density of mated females is rather high. Efforts to improve the efficacy of MD are ongoing with a small cadre of researchers.